2019
DOI: 10.1021/acsnano.8b09781
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Size and Coating Chemistry Control Foliar Uptake Pathways, Translocation, and Leaf-to-Rhizosphere Transport in Wheat

Abstract: Nanoenabled foliar-applied agrochemicals can potentially be safer and more efficient than conventional products. However, limited understanding about how nanoparticle properties influence their interactions with plant leaves, uptake, translocation through the mesophyll to the vasculature, and transport to the rest of the plant prevents rational design. This study used a combination of Au quantification and spatial analysis to investigate how size (3, 10, or 50 nm) and coating chemistry (PVP versus citrate) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
376
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(431 citation statements)
references
References 75 publications
23
376
2
Order By: Relevance
“…For that reason, only species able to cross the cuticle or penetrate through stomata (lacking cuticle coat) can be internalized in the leaves. In agreement with previous reports [54,55], our results confirm that nanoparticle surface dissolution (and consequently nutrient release) is not necessarily a limiting step to allow nutrients uptake through the leaves. This opens the door to the future development of ACP functionalized with other active species (besides fertilizers) for foliar applications.…”
Section: Nanoparticles Uptake and Localization In Wheat Plantssupporting
confidence: 93%
“…For that reason, only species able to cross the cuticle or penetrate through stomata (lacking cuticle coat) can be internalized in the leaves. In agreement with previous reports [54,55], our results confirm that nanoparticle surface dissolution (and consequently nutrient release) is not necessarily a limiting step to allow nutrients uptake through the leaves. This opens the door to the future development of ACP functionalized with other active species (besides fertilizers) for foliar applications.…”
Section: Nanoparticles Uptake and Localization In Wheat Plantssupporting
confidence: 93%
“…Stomata may take up water and solutes, and even small particles may penetrate leaves through stomata. The mechanisms behind this process are still not fully understood (Avellan et al 2019;. It is possible that the uptake occurs by diffusion through a liquid water film in the stomata walls, which are formed by increasing the wettability of the stomata pores (Burkhardt 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…They found that "regardless of their coating and sizes, the majority of the transported AuNPs accumulated in younger shoots (10-30%) and in roots (10-25%), and 5-15% of the NPs <50 nm were exuded into the rhizosphere soil. A greater fraction of larger sizes AuNPs (presenting lower ζ potentials) was transported to the roots" (Avellan et al, 2019).…”
Section: Nanocrystalsmentioning
confidence: 99%